Pembentukan Karakter Sosial Peserta Didik Melalui Kegiatan Ekstrakurikuler di SMP Nahdlatul Ulama Simo Karanggeneng - Fifit Rohmawati; Sulhatul Habibah; Hurin Innihayatus Sa'adah (AJER: Advanced Journal of Education and Religion, 2025)
The importance of character education in developing students who are not only academically smart but also prossess strong moral and social values. Currently, many students still experience deficient social behavior, such as a lack of discipline, disrespecting and not appreciating others, using foul language, and so on. Therefore, educational strategies are needed that focus not only on academics but also on developing students’ social character. One effort that can be done is trough extracurricular activities. This study aims to describe the process of social character formation in students through extracurricular activities at Nahdlatul Ulama Simo Karanggeneng Junior High School and to analyze the supporting and inhibiting factors in this process. In this study, the researcher used a descriptive qualitative method, and data collection techniques included observations, interviews, and documentation. The results indicate that the process of social character formation in students through extracurricular activities at Nahdlatul Ulama Simo Karanggeneng Junior High School occurs in stages: introduction, understanding and application, and habituation. Supporting factor s for social character formation through extracurricular activities include high students interest in participating in extracurricular activities, school support, and facilities and infrastructure. Meanwhile, inhibiting factors for social character formation trough extracurricular activities include the external environment, the individual, the family environment.